1995
DOI: 10.1002/ijch.199500015
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Shear Response in Nanometer‐Thick Films

Abstract: Simulations of the structure and dynamics of fluid films confined to a thickness of a few molecular diameters are described. Confining walls introduce layering and in-plane order in the adjacent fluid. The latter is essential to transfer of shear stress. As the film thickness is decreased, by increasing pressure or decreasing the number of molecular layers, the entire film may undergo a phase transition. Spherical molecules tend to crystallize, while short chain molecules enter a glassy state with strong local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
163
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(182 citation statements)
references
References 62 publications
(199 reference statements)
16
163
3
Order By: Relevance
“…26 In most of our simulations, the sheared fluid is not thermostatted and only the confining walls are maintained at a specified temperature by coupling the motion of their atoms to a heat bath. 18 In order to investigate the effects of thermostatting on the viscosity of the fluid, a set of simulations was also performed by using a thermostatting scheme reported in literature 17,19 where, in addition to the walls, the fluid is also kept at a constant temperature by coupling the y component of the equation of motion of its atoms to a heat bath maintained at the desired temperature. ͑Note that we do not advocate the use of this particular type of thermostat; we only use it to compare our results to those published in the literature.͒ This is achieved by adding Langevin noise and frictional terms to the equation of motion in the y direction:…”
Section: Simulation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…26 In most of our simulations, the sheared fluid is not thermostatted and only the confining walls are maintained at a specified temperature by coupling the motion of their atoms to a heat bath. 18 In order to investigate the effects of thermostatting on the viscosity of the fluid, a set of simulations was also performed by using a thermostatting scheme reported in literature 17,19 where, in addition to the walls, the fluid is also kept at a constant temperature by coupling the y component of the equation of motion of its atoms to a heat bath maintained at the desired temperature. ͑Note that we do not advocate the use of this particular type of thermostat; we only use it to compare our results to those published in the literature.͒ This is achieved by adding Langevin noise and frictional terms to the equation of motion in the y direction:…”
Section: Simulation Methodsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] These can be classified into two broad categories: homogeneous shear methods and boundary driven shear methods. Homogeneous shear methods 11 impart shear on a fluid by modifying the equations of motion and employing ''sliding brick'' periodic boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such solid sliding is a major cause of frictional dissipation, and can persist even in the presence of lubricants (1). At a nanotribological level, surface force balance (SFB) measurements, supported by theory and computer simulations, have shown that when simple organic liquids are confined between atomically smooth, solid (mica) surfaces to films thinner than some six to eight molecular layers, they may become solid-like, and are often layered (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Subsequent sliding of the surfaces across such films when they are subjected to shear may then take place via stick-slip motion (15,16).…”
mentioning
confidence: 99%